Penerapan Metode Analytical Hierarchical Process Pada Sistem Pendukung Keputusan Prestasi Belajar Siswa (Studi Kasus SD Negeri 17 Gunung Megang) - Fadillah, Sahla; Andi Christian; Ariansyah (Elkom: Jurnal Elektronika dan Komputer, 2023)
Achievement ability is a pinnacle of the learning process, at this stage students prove the success of learning at school SD Negeri 17 Gunung Megang. However, as the learning process progresses, several things occur that can affect this success. One of them is the problem of declining achievement scores, both academic and non-academic scores. The value of achievement that decreases or increases can be influenced by various factors. All problems need to be resolved so that the school can find a solution to increase or maintain the value of student achievement for the next period. Based on these problems, a Decision Support System is needed that can help the school in seeing the effect of student achievement. The method used in making decisions on the effect of student achievement is the Analytical Hierarchy Process (AHP) method. AHP can be compiled based on a hierarchical model that is made together with decision makers in order to provide solutions through the highest weight value in each criterion and alternative that is served. The decision support system with the AHP method can determine the priority weight of the criteria.